Hyperspectral scanning imaging index from sediment core HZM19, Holzmaar (West-Eifel Volcanic Field, Germany) - María Luján García; Stella Birlo; Petra Zahajská; Giulia Wienhues; Martin Grosjean; Bernd Zolitschka (PANGAEA, 2024)
Pigments measurements (RABD671 and RABD845) were made by Specim PFD-CL-65V10E linescan camera following the methods of (Butz et al., 2015, doi:10.1117/1.JRS.9.096031), at a resolution of 60 exttimes 60 μm. Scanning methodology and index calculations can be found in (Zander et al., 2021, doi:10.1016/j.scitotenv.2020.143713). The sediment core HZM19 was collected in 2019, from Holzmaar, West-Eifel Volcanic Field in Germany using a UWITEC Piston Corer. The sediment core was collected to reconstruct environmental and climate changes of Holzmaar for the last 16,000 years cal BP. Particularly in this data set we cover between 2450-2950 cal BP.